Torsion modulus with CaCO3 fillers in unsaturated polyester resin - mechanical spectroscopy - Pintao, Carlos Alberto Fonzar [UNESP]; Baggio, Airton [UNESP]; Piedade, Lucas Pereira [UNESP]; Sanchez, Luiz Eduardo de Angelo [UNESP]; Goncalves, Gilberto de Magalhaes Bento [UNESP] (Assoc Brasil Polimeros, 2022)
This work presents an alternative to studying and determining the torsion modulus, G, in composites. For this purpose, we use a measuring system with a rotation motion sensor coupled with a torsion pendulum that allows for determining the angular position as a function of the time. Then, through an equation derived from mechanical spectroscopy studies that permits the calculation of G's value, the experiments focus on samples of different quantities of calcium carbonate (CaCO3) in unsaturated polyester resins. The results show that CaCO3 (33.33%W) fillers increase G's value by 88% compared with unsaturated resin (100%W). Furthermore, there is a density increase of approximately 21% with the addition of CaCO3, considering the same two samples, which makes these composites the most massive. The relationship between G and composite density shows that it is possible to change the amount of CaCO3 to increase torsion resistance values in a controlled way.
Keywords: Calcium carbonate; Mechanical spectroscopy; Polyester resin; Torsion modulus